2014
DOI: 10.1002/jcu.22153
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlation needed: What do emergency physicians do after an equivocal ultrasound for pediatric acute appendicitis?

Abstract: We view our study as a fundamental part of the incremental progress to understand how best to use US and CT imaging to diagnose pediatric appendicitis while minimizing ionizing radiation. Children at low risk for appendicitis with equivocal US are amenable to observation and reassessment prior to reimaging with US or CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…A recent study from the Stanford Emergency Department has shown that children with equivocal US may be amenable to observation [27], but the study is limited by using CT as their primary end-point rather than the positive or negative outcome of appendicitis. Our study is the first that we know of, to date, to look at the relationship of a non-diagnostic US and the primary outcome of the presence or absence of appendicitis.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study from the Stanford Emergency Department has shown that children with equivocal US may be amenable to observation [27], but the study is limited by using CT as their primary end-point rather than the positive or negative outcome of appendicitis. Our study is the first that we know of, to date, to look at the relationship of a non-diagnostic US and the primary outcome of the presence or absence of appendicitis.…”
Section: Discussionmentioning
confidence: 97%
“…Both grayscale and color Doppler imaging are utilized with 5-MHz curved, 9-MHz linear, or 15-MHz linear transducers [58] . Ultrasound is 88% sensitive and 94% specific for the diagnosis of acute appendicitis [59] . Diagnostic criteria for appendicitis include appendiceal diameter > 6 mm (outer wall to outer wall) and associated evidence of inflammation including appendiceal non-compressibility, wall thickening > 2 mm or hyperemia, fluid-filled appendix, increased echogenicity of periappendiceal fat, and/or presence of periappendiceal fluid [58] .…”
Section: A B C Dmentioning
confidence: 99%
“…Ultrasound diagnosis of perforated appendicitis is made by the presence of marked inflammatory changes in the right lower quadrant with or without visualization of the appendix, an appendicolith without visualization of the appendix, echogenic free fluid, or a fluid collection indicating peritonitis or abscess [58] . Equivocal findings on ultrasound are associated with surgical appendicitis in 12.5%-50% of cases [58,59] . Increasing the size threshold to 7.5-8 mm in equivocal cases has been shown to increase specificity and accuracy [58,60] .…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation
“…While dedicated paediatric sonographers are more likely than their general counterparts to locate the appendix,32, 33 many children do not present to specialist paediatric departments. Definitive sonographic criteria or techniques that improve accuracy and assist diagnosis would be of particular benefit in these cases.…”
Section: Introductionmentioning
confidence: 99%